O método de Leo Strauss de leitura dos diálogos de Platão: um estudo a partir da República - Rodrigues, Tiago Azambuja (2021)
This work is devoted to Leo Strauss' method of reading Plato's dialogues. We reconstructed it in a pedagogical way, that is, in conjunction with Strauss' famous and controversial interpretation of the Republic, in order to elucidate the “praxis” itself (the operation or functioning) of the author's hermeneutics. As we interpret this method, it consists of three general principles: i) irony, ii) comicality and iii) logographic necessity. Based on these principles, it is a reading that addresses Plato's dialogues in view of their dramatic nature and not only their philosophical content. For this reason, the “Strauss reader of Plato” is part of the (recent) dialogical tradition of reading dialogues, which revisits and revives the literary and dramatic question of platonic writings. Therefore, it is essential, especially for the reader unfamiliar with Strauss' approach, to understand the relationship of strict connection and dependence between his way of reading the dialogues and the interpretation of the Republic proposed by him. Strauss' interpretation of Politeia is dramatic, it turns to the plot and its action. According to him, the main action of the dialogue is the action of Gláucon, which concerns the remission of extreme political ambition. It is also the purge of Plato's reader, who goes through the same catharsis as the character. This purpose is achieved by Plato's Socrates through the kallipolis “experiment”, which, if well understood, serves to show the limits and nature of political or city reality (polis). The beautiful city, as seen by Strauss, is ironic, as it deliberately conceals about the body or is constructed in abstraction, or deliberate disregard for eros. The erotic-affective reality of man (corporeality) shows that kallipolis, which requires the community of property and family, is impossible, that because the limitations imposed by the body cannot be overcome. Likewise, the philosophers' eros, eros in a noble sense, leads them to contemplative life and in opposition to the things of the city. Plato's attentive reader, the potential philosopher, being able to understand this message learns about the nature and limits of political things. He learns that the thirst for justice, in all its intensity, cannot be quenched by political ideals, but by philosophical life, the truly just life, which is withdrawn life.